The tomato gene Ty-6, encoding DNA polymerase delta subunit 1, confers broad resistance to Geminiviruses - Xuexue Shen; Upinder Gill; Marjon Arens; Zhe Yan; Yuling Bai; Samuel F. Hutton; Anne-Marie A. Wolters (Theoretical and Applied Genetics, 2025)
Key message The tomato Ty-6 gene conferring resistance against begomoviruses has been cloned and shown to be a variant of DNA polymerase delta subunit 1. Abstract Ty-6 is a major resistance gene of tomato that provides resistance against monopartite and bipartite begomoviruses. The locus was previously mapped on chromosome 10, and in this study, we fine-mapped Ty-6 to a region of 47 kb, including four annotated candidate genes. Via whole-genome resequencing of Ty-6 breeding lines and several susceptible breeding lines, the polymorphisms in gene sequences were discovered and gene-associated markers were developed for marker-assistant breeding. Further, virus-induced gene silencing and candidate gene overexpressing in susceptible tomatoes revealed that Ty-6- mediated resistance is controlled by Solyc10g081250, encoding the DNA polymerase delta subunit 1, SlPOLD1 . The single nucleotide polymorphism of Ty-6 results in an amino acid change that might influence the fidelity of virus DNA replication.

Characterization and elimination of linkage-drag associated with Fusarium wilt race 3 resistance genes - Jessica Chitwood-Brown; Gary E. Vallad; Tong Geon Lee; Samuel F. Hutton (Theoretical and Applied Genetics, 2021)
Key message Reducing the size of the I-3 introgression resulted in eliminating linkage-drag contributing to increased sensitivity to bacterial spot and reduced fruit size. The I-7 gene was determined to have no effect on bacterial spot or fruit size, and germplasm is now available with both the reduced I-3 introgression and I-7. Abstract Tomato ( Solanum lycopersicum ) production is increasingly threatened by Fusarium wilt race 3 ( Fol3 ) caused by the soilborne fungus, Fusarium oxysporum f. sp. lycopersici . Although host resistance based on the I-3 gene is the most effective management strategy, I-3 is associated with detrimental traits including reduced fruit size and increased bacterial spot sensitivity. Previous research demonstrated the association with bacterial spot is not due to the I-3 gene, itself, and we hypothesize that reducing the size of the I-3 introgression will remedy this association. Cultivars with I-7 , an additional Fol3 resistance gene, are available but are not widely used commercially, and it is unclear whether I-7 also has negative horticultural associations. To characterize the effect of I-3 on fruit size, segregating populations were developed and evaluated, revealing that the large I-3 introgression decreased fruit size by approximately 21%. We reduced the I-3 introgression from 5 to 140 kb through successive recombinant screening and crossing efforts. The reduced I-3 introgression and I-7 were then separately backcrossed into elite Florida breeding lines and evaluated for effects on bacterial spot sensitivity and fruit size across multiple seasons. The reduced I-3 introgression resulted in significantly less bacterial spot and larger fruit size than the large introgression, and it had no effect on these horticultural characteristics compared with Fol3 susceptibility. I-7 was also found to have no effect on these traits compared to Fol3 susceptibility. Together, these efforts support the development of superior Fol3 -resistant cultivars and more durable resistance against this pathogen.

Ty-6, a major begomovirus resistance gene on chromosome 10, is effective against Tomato yellow leaf curl virus and Tomato mottle virus - Upinder Gill; John W. Scott; Reza Shekasteband; Eben Ogundiwin; Cees Schuit; David M. Francis; Sung-Chur Sim; Hugh Smith; Samuel F. Hutton (Theoretical and Applied Genetics, 2019)

Linkage between the I-3 gene for resistance to Fusarium wilt race 3 and increased sensitivity to bacterial spot in tomato - Jian Li; Jessica Chitwood; Naama Menda; Lukas Mueller; Samuel F. Hutton (Theoretical and Applied Genetics, 2018)

Identification of QTL associated with resistance to bacterial spot race T4 in tomato - Samuel F. Hutton; Jay W. Scott; Wencai Yang; Sung-Chur Sim; David M. Francis; Jeffrey B. Jones (Theoretical and Applied Genetics, 2010)